2008
DOI: 10.1149/1.2953525
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Activation of Expanded Graphite Electrode for Electrochemical Capacitor

Abstract: An expanded graphite ͑e-MCMB, mesocarbon microbeads͒ having a wider interlayer spacing ͑d 002 = 0.404 nm͒ than that of common graphites is prepared by heat-treatment of an oxidized MCMB. When the e-MCMB electrode, which gives a negligible capacitance due to a small surface area, is polarized over a certain onset potential ͓4.6-4.8 V ͑vs Li/Li + ͒ for positive and 1.3-1.0 V for negative direction͔, it is electrochemically activated to be a high-capacitance positive and negative electrode for electrochemical cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 49 publications
2
37
1
Order By: Relevance
“…This review mainly focuses on the opening of 2D materials and their subsequent applications in energy conversion and storage fields, expecting to promote the development of such a new class of materials, namely expanded 2D materials. [17] In addition, Seung et al prepared an expanded graphite with a larger interlayer spacing (d 002 = 0.404 nm), [18] and it was concluded that the prerequisite for electrochemical activation was the expansion of interlayer distance in graphitic carbons. Furthermore, prospects and further developments in these exciting fields of the expanded 2D materials are also commented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review mainly focuses on the opening of 2D materials and their subsequent applications in energy conversion and storage fields, expecting to promote the development of such a new class of materials, namely expanded 2D materials. [17] In addition, Seung et al prepared an expanded graphite with a larger interlayer spacing (d 002 = 0.404 nm), [18] and it was concluded that the prerequisite for electrochemical activation was the expansion of interlayer distance in graphitic carbons. Furthermore, prospects and further developments in these exciting fields of the expanded 2D materials are also commented.…”
Section: Introductionmentioning
confidence: 99%
“…For example, experimental results from Zhang et al showed that the electrical transport properties of MoS 2 nanosheets could be tuned by intercalating phosphorus atoms (P). [17] In addition, Seung et al prepared an expanded graphite with a larger interlayer spacing (d 002 = 0.404 nm), [18] and it was concluded that the prerequisite for electrochemical activation was the expansion of interlayer distance in graphitic carbons.In this review, we mainly focus on how to open 2D materials and their subsequent applications in energy conversion and storage fields, hoping to promote the development of expanded 2D material (Scheme 1). To begin with, a variety of methods for opening 2D materials are described.…”
mentioning
confidence: 99%
“…In the development of electrochemical double layer capacitor (EDLC), many materials have been used as electrode active material like carbon aerogel [20,21], manganese oxide (MnO 2 ) [22], graphite [5,23] and activated carbon [24][25][26]. However, activated carbon is preferred due to its outstanding properties such as high surface area, low cost, high conductivity and good chemical stability [26].…”
Section: Introductionmentioning
confidence: 99%
“…EG has been investigated owing to its unique properties in terms of excellent electrical conductivity, good chemical stability, cheap price, relatively wider interlayer spacing and larger specific surface area as compared to graphite [31]. Guo et al [32] prepared AC/EG composite by a novel supersonic wave shocking method, the largest specific capacitance (Cs) can reach to 305 F/g at 1 mA charging current.…”
Section: Introductionmentioning
confidence: 99%